Heterotopic pregnancy. Presentation of four cases (Colombia Medica, 2024)
Heterotopic pregnancy is defined as intrauterine and extrauterine pregnancy entity coexisting simultaneously and which has been on the rise in recent years with the development of assisted reproductive techniques. We report 4 cases of heterotopic pregnancy, three of them resulting from assisted reproductive technologies and a spontaneous case. We also describe the methods used for diagnosis, therapies and behavior and perinatal outcome.